2018
DOI: 10.1002/jcc.25205
|View full text |Cite
|
Sign up to set email alerts
|

Accurate lattice energies of organic molecular crystals from periodic turbomole calculations

Abstract: Accurate lattice energies of organic crystals are important i.e. for the pharmaceutical industry. Periodic DFT calculations with atom-centered Gaussian basis functions with the Turbomole program are used to calculate lattice energies for several non-covalently bound organic molecular crystals. The accuracy and convergence of results with basis set size and k-space sampling from periodic calculations is evaluated for the two reference molecules benzoic acid and naphthalene. For the X23 benchmark set of small mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…CP corrections also showed that a basis set error (BSSE) for the def2-TZVP basis set was, at most, 7% of the interaction energy of molecular compounds in the crystal. This reduced the calculated lattice energy and brought it even closer to experiment [23]. Further work on the implementation of the BSSE correction into periodic DFT with Gaussian basis functions is ongoing.…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…CP corrections also showed that a basis set error (BSSE) for the def2-TZVP basis set was, at most, 7% of the interaction energy of molecular compounds in the crystal. This reduced the calculated lattice energy and brought it even closer to experiment [23]. Further work on the implementation of the BSSE correction into periodic DFT with Gaussian basis functions is ongoing.…”
Section: Methodsmentioning
confidence: 94%
“…The lattice energies for the organic molecules of the X23 benchmark set and related chiral compounds were found to have almost converged using the medium-sized, triple-zeta def2-TZVP basis set; the larger def2-TZVPP basis set did not significantly change the calculated lattice energies for representatives of either the vdW, mixed, and hydrogen-bonded molecular classes [23]. CP corrections also showed that a basis set error (BSSE) for the def2-TZVP basis set was, at most, 7% of the interaction energy of molecular compounds in the crystal.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations